(untitled) (Universal International Scientific Journal, 2026)
.In this study, the synthesis of SrTiO₃ perovskite material via the sol–gel method in a DMSO medium and the influence of citric acid and yetmak plant extract used as stabilizers on its optical properties were investigated. The obtained samples were analyzed using photoluminescence (PL) spectroscopy. The PL spectra exhibited several emission maxima in the 400–1500 nm range. A strong emission band observed in the 550–600 nm region indicates the presence of defect states associated with oxygen vacancies and Ti³⁺ centers in the SrTiO₃ crystal lattice. The emission at higher wavelengths suggests the formation of deep energy levels and surface states. The results confirm that the use of citric acid and plant extract during synthesis increases the defect concentration in SrTiO₃ and significantly affects its optical activity.